PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN DENGAN INTELLECTUAL CAPITAL SEBAGAI VARIABEL INTERVENING - Ningsih, Kurnia; Hariyati, Hariyati (Jurnal Akuntansi AKUNESA, 2020)
The purpose of the research is to investigate the effect of financial performance on firm value with intellectual capital as an intervening variable. The samples in the research are 150 Companies listed in the Jakarta Islamic Index Period 2013-2017. This research used  regression with intervening variable and path analysis with SPSS 23 to test the hypothesis. The result of this research indicate that financial performance (ROE) has a positive effect on firm value (Tobins Q). financial performance also has a positive effect on intellectual capital (Modified-VAIC). Then financial performance (ROE) on firm value (Tobins Q) through intellectual capital (Modified-VAIC) have no effect.